2015
DOI: 10.1103/physrevlett.114.240401
|View full text |Cite
|
Sign up to set email alerts
|

Accurate and Robust Unitary Transformations of a High-Dimensional Quantum System

Abstract: Quantum control in large dimensional Hilbert spaces is essential for realizing the power of quantum information processing. For closed quantum systems the relevant inputoutput maps are unitary transformations, and the fundamental challenge becomes how to implement these with high fidelity in the presence of experimental imperfections and decoherence. For two-level systems (qubits) most aspects of unitary control are well understood, but for systems with Hilbert space dimension d>2 (qudits), many questions rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
67
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(68 citation statements)
references
References 32 publications
0
67
0
Order By: Relevance
“…Control strategies for spins in semiconductors currently trade off conceptually simple single-spin schemes [426,427] with more robust and accessible two-and three spin techniques [428][429][430]. The short natural time scales suggest adiabatic schemes to be attractive [431][432][433] In view of scaling up control, the design and implementation of unitary maps have recently been demonstrated in a 16-dimensional Hilbert space, spanned by the electron and nuclear spins of individual cesium atoms [434].…”
Section: State Of the Artmentioning
confidence: 99%
“…Control strategies for spins in semiconductors currently trade off conceptually simple single-spin schemes [426,427] with more robust and accessible two-and three spin techniques [428][429][430]. The short natural time scales suggest adiabatic schemes to be attractive [431][432][433] In view of scaling up control, the design and implementation of unitary maps have recently been demonstrated in a 16-dimensional Hilbert space, spanned by the electron and nuclear spins of individual cesium atoms [434].…”
Section: State Of the Artmentioning
confidence: 99%
“…Moreover, threshold investigations of the qudit toric code with noise-free syndrome measurements have shown that, for a standard independent noise model, the error correction threshold increases significantly with increasing qudit dimension [14][15][16], although we caution that it is difficult to fairly compare noise rates between systems of different dimensions. Although it is more challenging to realize qudit quantum systems experimentally, recent work has demonstrated the ability to coherently control and perform operations in single 16-dimensional atomic systems with high fidelity [17,18], with the implementation of high-fidelity multiqudit interactions still to be achieved.A surface code is a stabilizer code with local stabilizer generators. Qudits are associated with the edges of a 2D square lattice.…”
mentioning
confidence: 99%
“…The major two sources of errors that are expected for a spin qubit are the finite fidelity of gates and the uncontrolled environmental magnetic field fluctuations. The former problem is more important because there are already many single and few qubit platforms with long coherence times [8][9][10][11]. A non-perfect quantum gate can be characterized by the typical difference φ 0 between the rotation angle of a qubit and the desired angle π/n.…”
mentioning
confidence: 99%